Analisis Kampanye TikTok “BFI Senyum Ramadhan” Sebagai Pembangun Brand Awareness di BFI Finance - Francesca, Molly; Utami, Lusia Savitri Setyo (Prologia, 2022)
Today, many companies are turning to digital marketing. Promotions are also carried out through social media such as Tik Tok. Tik Tok as a social media is experiencing rapid development. According to statistics, there are 22.2 million active Tik Tok users in Indonesia. This makes Tik Tok a company promotion medium, one of which is the financing company BFI Finance. This company once held a Tik Tok campaign "BFI Smile Ramadhan" in an effort to build brand awareness. This research uses marketing communication theory, campaign concept, social media, and public relations. In this study, the research used a qualitative approach with a case study method. Data collection was carried out by in-depth interviews. Subjects to be interviewed include those from the Integrated Marketing Communication division of BFI Finance, followers of the Tik Tok @bfilir account and participants of the Tik Tok campaign "BFI Smile Ramadhan". The results of interviews with informants are that the campaign is one element of building brand awareness. Then, in building brand awareness, a good marketing strategy is needed. In this case market research is important to ensure a successful company campaign.   Seiring dengan perkembangan zaman, banyak perusahaan yang beralih ke pemasaran digital. Promosi pun dilakukan melalui media sosial seperti Tik Tok. Tik Tok sebagai media sosial mengakami perkembangan yang pesat. Melansir dari statistik ada 22,2 juta pengguna aktif Tik Tok di Indonesia. Hal ini membuat Tik Tok menjadi medium promosi perusahaan, salah satunya adalah perusahaan pembiayaan BFI Finance. Perusahaan ini yang sempat mengadakan kampanye Tik Tok “BFI Senyum Ramadhan” dalam usaha membangun brand awareness. Penelitian ini menggunakan teori komunikasi pemasaran, konsep kampanye, media sosial, serta public relations. Pada penelitian ini, penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Pengumpulan data dilakukan dengan wawancara mendalam. Subjek yang akan diwawancarai diantaranya dari divisi Integrated Marketing Communication BFI Finance, pengikut akun Tik Tok @bfilancar dan peserta kampanye Tik Tok “BFI Senyum Ramadhan”. Hasil dari wawancara dengan para informan adalah, kampanye adalah salah satu elemen membangu brand awareness. Lalu, dalam membangun brand awareness dibutuhkan strategi pemasaran yang bai. Dalam hal ini riset pasar penting untuk menjamin kampanye perusahaan yang sukses.